Transformation through tension: The moderating impact of negative affect on transformational leadership in teams. (September 2014) - Mitchell, Rebecca; Boyle, Brendan; Parker, Vicki; Giles, Michelle; Joyce, Pauline; Chiang, Vico
Transformational leadership has consistently been argued to enhance diverse team outcomes, yet related research has generated ambiguous findings. We suggest that effectiveness is enhanced in interprofessional teams when transformational leaders engender dynamics that are characterized by interprofessional motivation and openness to diversity. Drawing on the mood-as-information perspective, we argue that negative affective tone moderates the impact of these mediators on team effectiveness. Further, we suggest that this moderating role is such that conditions of high negative affect enhance the mediating role of interprofessional motivation, while low negative affect strengthens the mediating role of openness to diversity. In order to investigate these divergent effects, the current study develops a model of leadership and interprofessional team effectiveness through two pathways reflecting the parallel mediating effects of interprofessional motivation and openness to diversity, and a moderating role for negative affect. Findings from a survey-based study of 75 healthcare teams support the utility of this model.